Optimization of Bioethanol Production Using Whole Plant of Water Hyacinth as Substrate in Simultaneous Saccharification and Fermentation Process - Zhang, Qiuzhuo; Weng, Chen; Huang, Huiqin; Achal, Varenyam; Wang, Duanchao (Frontiers in Microbiology, 2016)
The whole plant of Water Hyacinth that had potential to remove heavy metals from wastewater was used as substrate for bioethanol production in the current study. It was found that acid pretreatment exhibited the most effective for reducing sugars production. An amount of 402.93 mg reducing sugars was achieved at optimal condition after pretreatment and enzymatic hydrolysis. A regression model was built to optimize the fermentation factors according to Response Surface Method (RSM) in Saccharification and Fermentation (SSF) process. The optimized condition for ethanol production by SSF process was fermented at 38.87℃ for 81.87 h when inoculated with 6.11 ml yeast. 1.291 g/L bioethanol could be achieved by our predicted model in optimal condition. Meanwhile, 1.289 g/L ethanol was produced, which showed reliability of presented regression model in this study. The optimization method discussed in the present study leading to relatively high bioethanol production could provide a promising way for Alien Invasive Species with high cellulose content.